Pola Pembuatan Kebijakan Pendidikan (Studi Multi Kasus pada Tiga Dinas Pendidikan di Sulawesi Utara) - Senduk, J.F. Endre (Jurnal Aplikasi Manajemen, 2008)
This research emphasizes the procedure of the educational policy making rather than its product, the focus of the research in that sence elaborated into the following questions: (1) how is the description of the existence of planning unit on the official structure?. (2) how is the description of analysis procedure and formulation of educational policy?. (3) how is the implementation procedures of educational policy?, and (4) how is the monitoring and evaluation procedure of educational policy? This research used qualitative approach with the study design of multi-cases. The research findings can be summarized as: (1) the activities of planning unit of official structure, (2) analysis procedure and educational policy formulation, (3) implementation procedure of educational policy, (4) monitoring procedure and evaluation of policy.